If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-8y + 6z + -7) = 0 Reorder the terms: -1(-7 + -8y + 6z) = 0 (-7 * -1 + -8y * -1 + 6z * -1) = 0 (7 + 8y + -6z) = 0 Solving 7 + 8y + -6z = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + 8y + -7 + -6z = 0 + -7 Reorder the terms: 7 + -7 + 8y + -6z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 8y + -6z = 0 + -7 8y + -6z = 0 + -7 Combine like terms: 0 + -7 = -7 8y + -6z = -7 Add '6z' to each side of the equation. 8y + -6z + 6z = -7 + 6z Combine like terms: -6z + 6z = 0 8y + 0 = -7 + 6z 8y = -7 + 6z Divide each side by '8'. y = -0.875 + 0.75z Simplifying y = -0.875 + 0.75z
| 2p-1=5p-10 | | 8z+22+13z=71 | | 9a=-9a^2-18 | | 11w=3740 | | 5+4*8= | | 14+(17+b)= | | 1+lx+1= | | 8x+14=126 | | 5(9g+2)=50 | | 2a=a+40 | | cos(3x-20)=sin(5x+6) | | f-1=-3x^2+2x-7 | | 8q^2+4q=7q^2-2q+27 | | 13d+6=6d+27 | | 3(x-9)=-10.8 | | 3(x-9)=10.8 | | 7(a+5)=73.5 | | y-54=7t | | X^2+12x-9= | | 43.2=6c-9 | | an=15+3(n-3) | | 7e-1=15.8 | | -10x+9y=11 | | 6x^4-12x^3=0 | | 3p=29.1 | | h-25=36 | | 3k+2(3k+2)=49 | | 2x+12+38=80 | | 5v^2-11v-12=0 | | -5x+2y=-14 | | 0.66+1=4x-0.33 | | -4(n+7)-6n=-98 |